Turning Legal Pluralism into State-Sanctioned Law: Assessing the Implications of the New Constitutions and Laws in Bolivia and Ecuador - Anna Barrera (German Institute of Global and Area Studies (GIGA), 2011)
Ethnically diverse societies have long faced the challenge of accommodating distinct and often conflictive normative orders within a single polity. Leaving the ideal of a single, homogeneous legal order aside, many Latin American states have recently acknowledged the right of indigenous peoples to practice and generate proper law. The ensuing question of how to address the challenges implied by this state-sanctioned form of legal pluralism is examined by a comparison of Bolivia and Ecuador in this paper. Similarities between cases can be identified as to the definition and limits of indigenous jurisdictions and the coordi-nation among legal authorities. Marked differences exist with regard to the status of in-digenous law, the ability to appeal indigenous rulings, and the incorporation of indige-nous legal cultures into the state's legal system. While the new frameworks constitute re-markable progress, their effects in the longer term will depend on the broader political context and the willingness to alter the long-established attitudes of justice operators and broader societies alike.
Keywords: 300; legal pluralism; constitutional change; judicial reform; indigenous peoples; plurinational state; Bolivia; Ecuador; Verfassung; Indigene Völker; Rechtsordnung; Verfassungsreform; Bolivien; Ecuador